Method for electrocatalytic reduction of nitrate by using modified ferrocobalt layered double hydroxide electrode material
By modifying the cobalt-iron layered double hydroxide electrode material with copper doping and oxygen vacancy design, the problem of low conversion efficiency of existing electrocatalysts under low-concentration nitrate conditions is solved, achieving the effect of low-voltage and high-efficiency conversion of nitrate to ammonia. It has high selectivity and high Faradaic efficiency and is suitable for the resource utilization of low-concentration nitrate.
Patent Information
- Application Number
- CN202511026958.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-10-28
AI Technical Summary
Existing electrocatalysts suffer from drawbacks when treating low-concentration nitrates, including high energy consumption, poor adaptability, low selectivity, low Faraday efficiency, low ammonia synthesis rate, poor ammonia conversion effect, and low nitrate removal rate. They are difficult to efficiently convert nitrates to ammonia under low voltage conditions.
A modified cobalt-iron layered double hydroxide electrode material is used as the working electrode. Through the synergistic effect of copper-doped cobalt-iron layered double hydroxide and oxygen vacancies, a tandem catalytic mechanism is formed to promote the conversion of nitrate to nitrite and nitrite to ammonia, inhibit the hydrogen evolution reaction, and improve the efficiency of electrocatalytic reduction of nitrate.
It achieves efficient conversion of nitrate to ammonia under low voltage and low nitrate concentration, with a maximum ammonia production rate of 0.095 mmol h⁻¹cm⁻² and a highest Faradaic efficiency of 95.6%. It features high selectivity and high Faradaic efficiency, low energy consumption, and good applicability, making it suitable for the resource utilization of nitrates of different concentrations.
Smart Images

Figure CN120844122A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalytic reduction of nitrate to ammonia synthesis technology, specifically relating to a method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material. Background Technology
[0002] Currently, the Haber-Bosch process is the main method for industrial ammonia synthesis; however, this method leads to significant fossil fuel consumption and carbon dioxide emissions. Electrochemical reduction ammonia synthesis driven by green energy electricity has become a promising method, mainly including nitrogen reduction reaction (NRR) and nitrate reduction reaction (NO3RR). Nitrogen reduction reaction (NRR) can produce green ammonia through electrocatalytic reduction of nitrogen under environmental conditions, but due to the poor solubility of nitrogen and the difficulty of activation, the ammonia yield and Faraday efficiency are both very low. Nitrate reduction reaction (NO3RR), through electrocatalysis, converts nitrates into ammonia, which can produce ammonia while treating nitrate pollution in water, achieving both environmental and economic benefits. Therefore, from an energy and environmental perspective, obtaining an electrochemical reduction technology for ammonia production driven by green energy electricity is of great significance for effectively consuming nitrates in wastewater and establishing a sustainable pathway for the formation of "green ammonia."
[0003] NO3RR is a complex reaction involving nine protons and eight electrons, with multiple intermediates and byproducts. The competition between the hydrogen evolution reaction (HER) and NO3RR limits its large-scale application, making the selection of suitable electrochemical systems and electrocatalysts crucial technologies for promoting NO3RR applications. In particular, the development of electrocatalysts with long-term stability, high activity, and selectivity has attracted widespread attention in order to address the issues of electrochemical feasibility and operating costs.
[0004] Currently, the electrocatalysts used are mainly metal catalysts, namely transition metals (such as those containing copper, cobalt, and iron) and alloys composed of them. However, due to the planar symmetric (D3h) resonance structure of nitrates, their nucleophilicity and binding affinity to metal catalysts are low, resulting in slow nitrate reduction kinetics. This means the electrocatalytic conversion rate of nitrate to nitrite is low, and the conversion of nitrite to ammonia is further hindered by the HER (ether-ether-reactive) process, thus limiting ammonia synthesis efficiency. Furthermore, for the technical problem of effectively converting low-concentration nitrates to ammonia at low potentials, the limited nitrate distribution near the working electrode leads to slow reaction kinetics and strong HER competition, resulting in existing electrocatalytic electrode materials exhibiting low selectivity, low Faradaic efficiency, and low ammonia synthesis rate when treating low-concentration nitrates. This, in turn, leads to high energy consumption, poor adaptability, low nitrate removal rate, and poor ammonia conversion effect. Therefore, obtaining an electrocatalytic reduction method for nitrate that is low in energy consumption, has good applicability, high nitrate removal rate, and good ammonia conversion effect is of great significance for achieving efficient conversion of nitrate of different concentrations into ammonia under low voltage conditions and for realizing economical production. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material, which is simple to operate, mild in conditions, environmentally friendly, low in energy consumption, has good applicability, high nitrate removal rate, and good ammonia conversion effect.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution.
[0007] A method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material, wherein the modified cobalt-iron layered double hydroxide electrode material is used as the working electrode to electrocatalytically reduce nitrate; the modified cobalt-iron layered double hydroxide electrode material includes nickel foam, the surface of which is loaded with copper-doped cobalt-iron layered double hydroxide, the copper-doped cobalt-iron layered double hydroxide having oxygen vacancies.
[0008] A further improvement to the above method, the preparation method of the modified cobalt-iron layered double hydroxide electrode material, includes the following steps: S1. Mix iron salt, cobalt salt, copper salt, triammonium citrate, urea, ammonium fluoride and water to obtain a mixed solution; S2. Place the nickel foam in the mixed solution obtained in step S1, let it stand, and carry out a hydrothermal reaction to obtain the modified cobalt-iron layered double hydroxide electrode material.
[0009] In a further improvement to the above method, in step S1, the molar ratio of the iron salt, cobalt salt, copper salt, triammonium citrate, urea, and ammonium fluoride is 1–2:1–2:0.6–0.8:0.5–0.7:7.5–8.5:3.75–4.75.
[0010] In a further improvement to the above method, in step S2, the temperature of the hydrothermal reaction is 120℃~130℃, and the time of the hydrothermal reaction is 12h~16h.
[0011] In a further improvement to the above method, in step S1, the iron salt is ferric nitrate nonahydrate, the cobalt salt is cobalt nitrate hexahydrate, the copper salt is copper nitrate trihydrate, the mixing time is 30 min to 60 min, and the mixing is carried out under stirring conditions.
[0012] The above method is further improved in step S2, where the settling time is 30 min to 60 min; after the hydrothermal reaction is completed, the following treatment is also included: the reaction product is washed alternately with water and ethanol, and then dried under vacuum conditions at a temperature of 50℃ to 60℃ for 4 h to 6 h; before the nickel foam is used, the following pretreatment is also included: the nickel foam is ultrasonically cleaned sequentially in hydrochloric acid, acetone, ethanol and deionized water, with each ultrasonic cleaning time being 10 min to 12 min, and then cleaned with ultrapure water and dried; the concentration of the hydrochloric acid is 1M to 3M.
[0013] The above method is further improved by wherein the electrocatalytic reduction treatment specifically comprises: constructing a three-electrode system using a modified cobalt-iron layered double hydroxide electrode material as the working electrode; and using the three-electrode system to perform an electrocatalytic reduction reaction on the nitrate solution to complete the conversion of nitrate and produce ammonia.
[0014] In a further improvement to the above method, the initial concentration of the nitrate solution is 5 mM to 40 mM, and the nitrate includes potassium nitrate.
[0015] The above method is further improved by adding an electrolyte to the three-electrode system during the electrocatalytic reduction reaction. The concentration of the electrolyte in the three-electrode system is 0.2M, and the electrolyte is potassium sulfate. The voltage during the electrocatalytic reduction reaction is controlled at -0.4V vs. RHE to -0.8V vs. RHE, and the time of the electrocatalytic reduction reaction is 3600s to 9000s.
[0016] The above method is further improved by including, in the three-electrode system, a platinum sheet as the counter electrode and saturated Ag / AgCl as the reference electrode.
[0017] Compared with the prior art, the advantages of the present invention are: To address the shortcomings of existing electrocatalytic electrode materials in treating low-concentration nitrates, such as high energy consumption, poor adaptability, low selectivity, low Faradaic efficiency, low ammonia synthesis rate, poor ammonia conversion effect, and low nitrate removal rate, this invention creatively provides a method for electrocatalytic reduction of nitrates using a modified cobalt-iron layered double hydroxide electrode material. The modified cobalt-iron layered double hydroxide electrode material is used as the working electrode for electrocatalytic reduction of nitrates. The modified cobalt-iron layered double hydroxide electrode material comprises nickel foam, with copper-doped cobalt-iron layered double hydroxides loaded on its surface. These copper-doped cobalt-iron layered double hydroxides possess oxygen vacancies. The modified cobalt-iron layered double hydroxide electrode material used in this invention, on the one hand, employs a copper-doped cobalt-iron layered double hydroxide design, cleverly forming a tandem catalytic mechanism with copper and cobalt dual sites. Specifically, the copper sites can reduce nitrate to nitrite, and then the cobalt sites further reduce nitrite to ammonia. Thus, the combined effect of copper and cobalt doping promotes and enhances the kinetics of the electrocatalytic nitrate reduction reaction, thereby achieving rapid ammonia conversion under low nitrate concentration conditions. On the other hand, the introduction of oxygen vacancies can greatly promote water dissociation and capture the HER intermediate (*H) for the electrocatalytic reduction of nitrate to ammonia, thus successfully inhibiting HER. In other words, through the synergistic mechanism of oxygen vacancies and copper doping, the electrode material maintains both a high ammonia synthesis rate and high selectivity for ammonia generation, ultimately exhibiting excellent electrocatalytic reduction of nitrate to ammonia activity under lower voltage conditions, and converting more nitrate to ammonia at low voltage and low nitrate concentration. The modified cobalt-iron layered double hydroxide electrode material used in this invention has advantages such as high selectivity, high Faradaic efficiency, and high ammonia synthesis rate. It can convert more nitrate into ammonia under low voltage and low nitrate concentration, and the maximum ammonia production rate is 0.095 mmol / h when used for electrocatalytic reduction of nitrate. -1 cm -2 The highest Faraday efficiency is 95.6%. The method of this invention uses a modified cobalt-iron layered double hydroxide electrode material as the working electrode to electrocatalytically reduce nitrates. It can achieve efficient resource utilization under different nitrate concentrations and has advantages such as simple operation, mild conditions, environmental friendliness, low energy consumption, good applicability, high nitrate removal rate, and good ammonia conversion effect. It is a widely applicable method for nitrate resource utilization with high practical value and promising application prospects. Attached Figure Description
[0018] Figure 1 This is a transmission electron microscope (TEM) image of the modified cobalt-iron layered double hydroxide electrode material prepared in Example 1 of the present invention.
[0019] Figure 2 This is a high-resolution transmission electron microscope image of the modified cobalt-iron layered double hydroxide electrode material prepared in Example 1 of the present invention.
[0020] Figure 3 This is the energy spectrum of the modified cobalt-iron layered double hydroxide electrode material prepared in Example 1 of the present invention.
[0021] Figure 4 The image shows the electron spin resonance spectrum of the modified cobalt-iron layered double hydroxide electrode material prepared in Example 1 of this invention.
[0022] Figure 5 This is a comparison chart showing the ammonia generation rate and Faraday efficiency of the modified cobalt-iron layered double hydroxide electrode material under different voltages in Example 1 of the present invention.
[0023] Figure 6 This is a comparison chart showing the ammonia generation rate and Faraday efficiency of the nickel-fed cobalt-iron layered double hydroxide electrode material in Example 1 of the present invention under different voltages.
[0024] Figure 7 This is a comparison chart showing the ammonia generation rate and Faraday efficiency of the cobalt-iron layered double hydroxide electrode material with oxygen vacancy modification supported on nickel foam in Example 1 of the present invention under different voltages.
[0025] Figure 8 This is a comparison chart showing the ammonia generation rate and Faraday efficiency of the nickel-fed copper-doped cobalt-iron layered double hydroxide electrode material in Example 1 of the present invention under different voltages.
[0026] Figure 9 This is a comparison chart showing the ammonia generation rate and Faraday efficiency of the modified cobalt-iron layered double hydroxide electrode material in Example 1 of the present invention under different nitrate concentrations. Detailed Implementation
[0027] The present invention will be further described below with reference to the accompanying drawings and specific preferred embodiments, but this does not limit the scope of protection of the present invention. All materials and instruments used in the following embodiments are commercially available.
[0028] Example 1: A method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material, specifically using the modified cobalt-iron layered double hydroxide electrode material as the working electrode to perform electrocatalytic reduction treatment of nitrate, includes the following steps: (1) A three-electrode system was constructed using modified cobalt-iron layered double hydroxide electrode material as the working electrode, saturated Ag / AgCl as the reference electrode, and a 1×1cm platinum sheet as the counter electrode; wherein the electrolytic cell was an H-type electrolytic cell, and the anode and cathode chambers were separated by a Nafion-117 proton exchange membrane.
[0029] (2) The nitrate solution was electrocatalytically reduced using the three-electrode system in step (1). Specifically, 50 mL of a mixture of potassium nitrate (KNO3) and potassium sulfate (K2SO4) was added to the electrolytic cell. The concentration of potassium nitrate in the mixture was 5 mM and the concentration of potassium sulfate was 0.2 M. Electrocatalytic reduction was carried out at 25 °C for 3600 s at voltages of -0.4, -0.5, -0.6, -0.7, and -0.8 V vs. RHE, respectively, to complete the electrolytic reduction conversion of nitrate and obtain ammonia. During the electrocatalytic reduction reaction, an electrochemical workstation (Shanghai Chenhua CHI 660E) was connected for testing. Cyclic voltammetry (CV) curve testing was first performed, with a scan range of -0.1 to -0.8 V vs. RHE and a scan rate of 50 mV s. -1 Then, chronocurrent electrolysis tests were performed at different voltages.
[0030] After the electrocatalytic reduction reaction was completed, the concentration of ammonia produced was quantitatively analyzed using a UV-Vis spectrophotometer.
[0031] Control group A: Nitrate was catalytically reduced using nickel foam-supported cobalt-iron layered double hydroxide electrode material instead of the modified cobalt-iron layered double hydroxide electrode material, with other conditions remaining the same.
[0032] Control group B: Nitrate was catalytically reduced using nickel foam-supported cobalt-iron layered double hydroxide electrode material with oxygen vacancy modification instead of the modified cobalt-iron layered double hydroxide electrode material, with other conditions remaining the same.
[0033] Control group C: Nitrate was catalytically reduced using a nickel foam-supported copper-doped cobalt-iron layered double hydroxide electrode material instead of the modified cobalt-iron layered double hydroxide electrode material, with all other conditions being the same.
[0034] In this embodiment, the modified cobalt-iron layered double hydroxide electrode material used includes nickel foam, the surface of which is loaded with copper-doped cobalt-iron layered double hydroxide, which has oxygen vacancies.
[0035] In this embodiment, the preparation method of the modified cobalt-iron layered double hydroxide electrode material includes the following steps: (1) Commercial nickel foam (2×4 cm) was washed sequentially in 1M HCl solution, ethanol, acetone and deionized water, and ultrasonically cleaned for 10 min each. After ultrasonic cleaning, it was cleaned with ultrapure water to obtain pretreated nickel foam, which was then dried for later use.
[0036] (2) Add 1 mmol of ferric nitrate nonahydrate, 1 mmol of cobalt nitrate hexahydrate, 0.6 mmol of copper nitrate trihydrate, 0.5 mmol of triammonium citrate, 7.5 mmol of urea and 3.75 mmol of ammonium fluoride to 50 mL of deionized water and stir for 30 min to obtain a mixed solution.
[0037] (3) Place the pretreated nickel foam obtained in step (1) into the mixed solution obtained in step (2) and let it stand for 30 minutes to obtain a reaction solution containing nickel foam.
[0038] (4) The reaction solution containing nickel foam obtained in step (3) was placed in a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 120 °C for 12 h. After the reactor cooled down, the reaction product was washed with water and ethanol alternately, and then dried under vacuum at 60 °C for 6 h to obtain the modified cobalt-iron layered double hydroxide electrode material, denoted as Cu-CoFe LDH-Ov.
[0039] In control group A, the preparation method of the nickel foam-supported cobalt-iron layered double hydroxide electrode material includes the following steps: (1) Commercial nickel foam (2×4 cm) was ultrasonically cleaned for 10 min each in 1M HCl solution, ethanol, acetone and deionized water. After ultrasonic cleaning, it was cleaned with ultrapure water to obtain pretreated nickel foam, which was then dried for later use.
[0040] (2) Add 1 mmol of ferric nitrate nonahydrate, 1 mmol of cobalt nitrate hexahydrate, 7.5 mmol of urea and 3.75 mmol of ammonium fluoride to 50 mL of deionized water and stir for 30 min to obtain a mixed solution.
[0041] (3) Place the pretreated nickel foam in the mixed solution obtained in step (2) and let it stand for 30 min to obtain a reaction solution containing nickel foam.
[0042] (4) The reaction solution containing nickel foam obtained in step (3) was placed in a 100 mL polytetrafluoroethylene reactor and reacted at 120 °C for 12 h. After the reactor cooled down, the reaction product was washed with water and ethanol alternately, and then dried under vacuum at 60 °C for 6 h to obtain nickel foam-supported cobalt-iron layered double hydroxide electrode material.
[0043] In control group B, the method for preparing the cobalt-iron layered double hydroxide electrode material supported on nickel foam with oxygen vacancy modification includes the following steps: (1) Commercial nickel foam (2×4 cm) was washed sequentially in 1M HCl solution, ethanol, acetone and deionized water, and ultrasonically cleaned for 10 min each. After ultrasonic cleaning, it was cleaned with ultrapure water to obtain pretreated nickel foam, which was then dried for later use.
[0044] (2) Add 1 mmol of ferric nitrate nonahydrate, 1 mmol of cobalt nitrate hexahydrate, 0.5 mmol of triammonium citrate, 7.5 mmol of urea and 3.75 mmol of ammonium fluoride to 50 mL of deionized water and stir for 30 min to obtain a mixed solution.
[0045] (3) Place the pretreated nickel foam obtained in step (1) into the mixed solution obtained in step (2) and let it stand for 30 minutes to obtain a reaction solution containing nickel foam.
[0046] (4) The reaction solution containing nickel foam obtained in step (3) was placed in a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 120 °C for 12 h. After the reactor cooled down, the reaction product was washed with water and ethanol alternately, and then dried under vacuum at 60 °C for 6 h to obtain nickel foam-supported cobalt-iron layered double hydroxide electrode material modified with oxygen vacancies.
[0047] In control group C, the preparation method of the nickel foam-supported copper-doped cobalt-iron layered double hydroxide electrode material includes the following steps: (1) Commercial nickel foam (2×4 cm) was washed sequentially in 1M HCl solution, ethanol, acetone and deionized water, and ultrasonically cleaned for 10 min each. After ultrasonic cleaning, it was cleaned with ultrapure water to obtain pretreated nickel foam, which was then dried for later use.
[0048] (2) Add 1 mmol of ferric nitrate nonahydrate, 1 mmol of cobalt nitrate hexahydrate, 0.6 mmol of copper nitrate trihydrate, 7.5 mmol of urea and 3.75 mmol of ammonium fluoride to 50 mL of deionized water and stir for 30 min to obtain a mixed solution.
[0049] (3) Place the pretreated nickel foam obtained in step (1) into the mixed solution obtained in step (2) and let it stand for 30 minutes to obtain a reaction solution containing nickel foam.
[0050] (4) The reaction solution containing nickel foam obtained in step (3) was placed in a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 120°C for 12 h. After the reactor cooled down, the reaction product was washed with water and ethanol alternately, and then dried under vacuum at 60°C for 6 h to obtain nickel foam-loaded copper-doped cobalt-iron layered double hydroxide electrode material.
[0051] Figure 1 This is a transmission electron microscope (TEM) image of the modified cobalt-iron layered double hydroxide electrode material prepared in Example 1 of this invention. From... Figure 1 As can be seen, the modified cobalt-iron layered double hydroxide electrode material of the present invention exhibits a layered structure.
[0052] Figure 2 This is a high-resolution transmission electron microscope (TEM) image of the modified cobalt-iron layered double hydroxide electrode material prepared in Example 1 of this invention. From... Figure 2 It can be seen that there is a crystal structure with a lattice spacing of 0.75 nm, which is the (003) crystal plane of cobalt-iron layered double hydroxide.
[0053] Figure 3 This is the energy spectrum of the modified cobalt-iron layered double hydroxide electrode material prepared in Example 1 of this invention. From... Figure 3 It can be seen that cobalt, iron, copper, and oxygen elements are evenly distributed on the electrode material.
[0054] Figure 4 This is the electron spin resonance spectrum of the modified cobalt-iron layered double hydroxide electrode material prepared in Example 1 of this invention. From... Figure 4 It can be seen that the modified cobalt-iron layered double hydroxide electrode material contains oxygen vacancies.
[0055] Figure 5 This is a comparison graph showing the ammonia formation rate and Faraday efficiency of the modified cobalt-iron layered double hydroxide electrode material in Example 1 of this invention under different voltages. From... Figure 5 It can be seen that at -0.6 V vs. RHE voltage, the modified cobalt-iron layered double hydroxide electrode material exhibits the highest ammonia production Faradaic efficiency, i.e., an ammonia production Faradaic efficiency of 95.6%, corresponding to an ammonia generation rate of 0.095 mmol h⁻¹. -1 cm -2 .
[0056] Figure 6 This is a comparison graph showing the ammonia formation rate and Faraday efficiency of the nickel-fed cobalt-iron layered double hydroxide electrode material in Example 1 of the present invention under different voltages. From... Figure 6 It can be seen that at -0.4 V vs. RHE voltage, the nickel foam-supported cobalt-iron layered double hydroxide electrode material exhibits the highest ammonia production Faradaic efficiency, i.e., an ammonia production Faradaic efficiency of 92.1%, corresponding to an ammonia generation rate of 0.014 mmol h⁻¹. -1 cm -2 .
[0057] Figure 7 This is a comparison graph showing the ammonia formation rate and Faraday efficiency of the cobalt-iron layered double hydroxide electrode material supported on nickel foam with oxygen vacancy modification in Example 1 of the present invention under different voltages. From... Figure 7 It can be seen that at -0.5 V vs. RHE voltage, the nickel foam-supported cobalt-iron layered double hydroxide electrode material with oxygen vacancy modification has the highest ammonia production Faradaic efficiency, namely, an ammonia production Faradaic efficiency of 82.37%, corresponding to an ammonia generation rate of 0.024 mmol h⁻¹. -1 cm -2 .
[0058] Figure 8 This is a comparison graph showing the ammonia formation rate and Faraday efficiency of the nickel-fed copper-doped cobalt-iron layered double hydroxide electrode material in Example 1 of this invention under different voltages. From... Figure 8 It can be seen that at -0.5 V vs. RHE voltage, the nickel foam-supported copper-doped cobalt-iron layered double hydroxide electrode material exhibits the highest ammonia production Faradaic efficiency, i.e., an ammonia production Faradaic efficiency of 90.87%, with a corresponding ammonia generation rate of 0.018 mmol h⁻¹. -1 cm -2 .
[0059] In addition, in this embodiment, the effect of the modified cobalt-iron layered double hydroxide electrode material on the treatment of nitrates of different concentrations was also investigated. Specifically, when the concentration of potassium nitrate in the mixed solution was 5 mM, 10 mM, 20 mM and 40 mM, the voltage during the electrocatalytic reduction reaction was -0.6 V vs. RHE, the time was 3600 s, and other conditions were the same.
[0060] Figure 9 This is a comparison graph showing the ammonia formation rate and Faraday efficiency of the modified cobalt-iron layered double hydroxide electrode material in Example 1 of this invention under different nitrate concentrations. From... Figure 9 It can be seen that within the concentration range of potassium nitrate (5 mM to 40 mM), the ammonia production faradaic efficiency of the modified cobalt-iron layered double hydroxide electrode material is higher than 80%.
[0061] In summary, the modified cobalt-iron layered double hydroxide electrode material used in the method of this invention has advantages such as high selectivity, high Faradaic efficiency, and high ammonia synthesis rate. It can convert more nitrate into ammonia under low voltage and low nitrate concentration, and the maximum ammonia production rate is 0.095 mmol / h when used for electrocatalytic reduction of nitrate. -1 cm -2The highest Faraday efficiency is 95.6%. This invention utilizes a modified cobalt-iron layered double hydroxide electrode material for the electrocatalytic reduction of nitrates. This method enables the resource utilization of nitrates of different concentrations (especially low-concentration nitrates) under low voltage, offering advantages such as low energy consumption, good applicability, high ammonia conversion efficiency, and high nitrate removal rate. It is a widely applicable method for the resource utilization of nitrates, with high practical value and promising application prospects. Furthermore, this method is simple to operate, operates under mild conditions, and is environmentally friendly, facilitating large-scale promotion and enabling economical production.
[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention using the methods and techniques disclosed above, or modify them into equivalent embodiments with equivalent changes, without departing from the spirit and technical essence of the present invention. Therefore, any simple modifications, equivalent substitutions, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention shall still fall within the protection scope of the technical solutions of the present invention.
Claims
1. A method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material, characterized in that, The method uses a modified cobalt-iron layered double hydroxide electrode material as the working electrode to perform electrocatalytic reduction of nitrate; the modified cobalt-iron layered double hydroxide electrode material includes nickel foam, the surface of which is loaded with copper-doped cobalt-iron layered double hydroxide, which has oxygen vacancies.
2. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to claim 1, characterized in that, The preparation method of the modified cobalt-iron layered double hydroxide electrode material includes the following steps: S1. Mix iron salt, cobalt salt, copper salt, triammonium citrate, urea, ammonium fluoride and water to obtain a mixed solution; S2. Place the nickel foam in the mixed solution obtained in step S1, let it stand, and carry out a hydrothermal reaction to obtain the modified cobalt-iron layered double hydroxide electrode material.
3. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to claim 2, characterized in that, In step S1, the molar ratio of the iron salt, cobalt salt, copper salt, triammonium citrate, urea and ammonium fluoride is 1-2:1-2:0.6-0.8:0.5-0.7:7.5-8.5:3.75-4.
75.
4. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to claim 3, characterized in that, In step S2, the temperature of the hydrothermal reaction is 120℃~130℃, and the time of the hydrothermal reaction is 12h~16h.
5. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to claim 4, characterized in that, In step S1, the iron salt is ferric nitrate nonahydrate, the cobalt salt is cobalt nitrate hexahydrate, and the copper salt is copper nitrate trihydrate. The mixing time is 30 min to 60 min, and the mixing is carried out under stirring conditions.
6. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to claim 5, characterized in that, In step S2, the settling time is 30 min to 60 min; after the hydrothermal reaction is completed, the following treatment is also included: the reaction product is washed alternately with water and ethanol, and then dried under vacuum conditions at a temperature of 50℃ to 60℃ for 4 h to 6 h; before the use of the foamed nickel, the following pretreatment is also included: the foamed nickel is ultrasonically cleaned in hydrochloric acid, ethanol, acetone and deionized water in sequence, with each ultrasonic cleaning time being 10 min to 12 min, and then cleaned with ultrapure water and dried; the concentration of the hydrochloric acid is 1M to 3M.
7. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to any one of claims 1 to 6, characterized in that, The electrocatalytic reduction process specifically involves: constructing a three-electrode system using a modified cobalt-iron layered double hydroxide electrode material as the working electrode; and using the three-electrode system to perform an electrocatalytic reduction reaction on a nitrate solution to complete the conversion of nitrate and produce ammonia.
8. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to claim 7, characterized in that, The initial concentration of the nitrate solution is 5 mM to 40 mM, and the nitrate includes potassium nitrate.
9. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to claim 8, characterized in that, The electrocatalytic reduction reaction process also includes adding an electrolyte to the three-electrode system. The concentration of the electrolyte in the three-electrode system is 0.2M, and the electrolyte is potassium sulfate. The voltage controlled during the electrocatalytic reduction reaction is -0.4V vs. RHE to -0.8V vs. RHE, and the time of the electrocatalytic reduction reaction is 3600s to 9000s.
10. The method for electrocatalytic reduction of nitrate using a modified cobalt-iron layered double hydroxide electrode material according to claim 9, characterized in that, The three-electrode system also includes: a platinum sheet as the counter electrode and saturated Ag / AgCl as the reference electrode.